Importance of Dissolved Methane Management When Anaerobically Treating Low-Strength Wastewaters - Shin, Chungheon; L. McCarty, Perry; Bae, Jaeho (Current Organic Chemistry, 2016)
This review indicates that although anaerobic treatment has the advantage of methane energy production, release of effluent dissolved methane into the atmosphere results in unwanted greenhouse gas (GHG) emissions. Reported concentrations of dissolved methane are 8 – 40 mg/L, accounting for about half of the total methane production from the treatment of low strength wastewaters. The dissolved fraction of the methane produced is affected by several factors such as reactor type, influent organic concentration, hydraulic retention time (HRT), solids retention time (SRT), temperature, influent sulfate concentration, and reactor mixing conditions. In addition, oversaturation with methane is typical for reactors without membranes or when operated at short HRT. If dissolved methane is not recovered, GHG emissions from anaerobic treatment could be much greater than that from conventional activated sludge treatment. The recovery of dissolved methane is essential in order to enhance energy production as well as to reduce GHG emissions when anaerobically treating for low strength wastewater.
Keywords: GHG emission